Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/ac040099i
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Mass Spectrometry Identified Bacterial Biomarkers from a Fielded Pyrolysis-Gas Chromatography-Ion Mobility Spectrometry Biodetector with the Microbiological Gram Stain Classification Scheme

Abstract: Public reporting burden for fthi collection of Informaiaon is estimated to, average I hour per response, including the time for reviewing Instructions. searchilng erristing data sources, gatheing and maintsteng the data needed, and completing and review"n this collection of Information. Send cofmment regarding this burden estimate or any othier aspect of this collection of Infomuation, Indluding suggestions for reducing fti burden to Departmrent PERFORMING ORGANIZATION NAME(S) AND ADDRESS(ES) AND ADDRESS(ES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
4
46
0
1
Order By: Relevance
“…Os pirogramas obtidos para os três tipos de bactérias estudados foram analisados, encontrando-se sinais característicos (biomarcardores) de tipos diferentes de bactérias, como o ácido tetradecanóico, tridecan-2-ona e dodecanal, que são compostos usados para distinguir bactéria gram-negativa (E. coli) de outras bactérias gram-positivas, como M. luteus e B. megaterium. 52 Alves et al 53 aplicaram a pirólise analítica para determinar o conteúdo de lignina em madeira de duas espécies de pinho Marítimo (Pinus pinaster e Picea abies). Os resultados obtidos com a pirólise analítica foram compatíveis com os teores de lignina Klason determinados pelo método (TAPPI T 222 OM-88), que é largamente utilizado como padrão para esse tipo de análise.…”
Section: Figura 8 Fluxograma Da Análise Por Pi-cg-em De Amostras Polunclassified
“…Os pirogramas obtidos para os três tipos de bactérias estudados foram analisados, encontrando-se sinais característicos (biomarcardores) de tipos diferentes de bactérias, como o ácido tetradecanóico, tridecan-2-ona e dodecanal, que são compostos usados para distinguir bactéria gram-negativa (E. coli) de outras bactérias gram-positivas, como M. luteus e B. megaterium. 52 Alves et al 53 aplicaram a pirólise analítica para determinar o conteúdo de lignina em madeira de duas espécies de pinho Marítimo (Pinus pinaster e Picea abies). Os resultados obtidos com a pirólise analítica foram compatíveis com os teores de lignina Klason determinados pelo método (TAPPI T 222 OM-88), que é largamente utilizado como padrão para esse tipo de análise.…”
Section: Figura 8 Fluxograma Da Análise Por Pi-cg-em De Amostras Polunclassified
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Some of the products have extremely high molecular weight, but there are also a number of low molecular weight, high volatility species that are produced. As would be expected, the lower molecular weight species prevail when the pyrolysis temperature is high and the residence time is long.…”
Section: Feasibility Of Using Swir Crds To Detect Biological Agent Pymentioning
confidence: 99%
“…Comparisons of the chromatograms from the bacteria showed that some peaks, or constituents in the chromatograms were observed in two or more strains of bacteria and should be associated with parts of the bacterial cells found generally in bacteria, e.g. 2-furancarboxaldehyde, a product from the pyrolysis of carbohydrates or phenol which is derived from proteins [29]. These chemicals may be useful in a cursory survey of biological versus non-biological, and might serve to indicate certain bacteria.…”
Section: Py-gc/fid Of Three Bacteria Samplesmentioning
confidence: 99%